Electrolyte, sodium ion battery and electric equipment
By using specific proportions and concentrations of sodium sulfonate and fluorine-containing sodium salt additives in sodium ion batteries, the deposition of sodium metal on the surface of the negative electrode sheet and the formation of SEI film are improved, and the problem of poor density of conductive coatings is solved, and the problem of improved density is improved. Charging and discharge efficiency and cycling performance of sodium ion batteries.
Patent Information
- Application Number
- CN202411547303.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2024-12-31
AI Technical Summary
The traditional negative electrode sheet has limited its application due to the volume expansion of the silicon-based material in the active material layer, resulting in poor density and rough surface in the negative electrode battery system, reducing the first charge and discharge efficiency of sodium ion batteries.
Using an electrolyte containing sodium sulfonate salt and sodium fluorine-containing salt as additives, the deposition density of sodium metal on the surface of the negative electrode sheet is improved by adjusting its mass ratio and concentration, and a stable SEI is formed during the charge and discharge process. The film is used to isolate the sodium metal layer and improve the circulation performance of the sodium ion battery.
It significantly improves the first charge and discharge efficiency and cycling performance of sodium ion batteries, reduces the loss of sodium metal, enhances the adhesion performance of the sodium metal layer and the negative electrode sheet, and extends the service life of the battery.
Smart Images

Figure CN119230940A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to an electrolyte, a sodium ion battery and electrical equipment. Background Art
[0002] With the development of battery technology, in order to meet the demand for higher energy density, the application of traditional negative electrode plates is limited due to the volume expansion of silicon-based materials in the active material layer. Therefore, the negative electrode-free battery system has become a new research direction. In the negative electrode-free system, the negative electrode is mainly coated with a conductive layer current collector. During the battery charging process, the sodium ions released from the positive electrode are deposited on the conductive coating to form a sodium metal negative electrode. Since there is no active material layer, the mass and volume of the negative electrode can be greatly reduced to improve the energy density of the battery. However, the conductive coating has poor density and a rough surface, and the adhesion performance of sodium on the conductive coating is poor, which reduces the initial charge and discharge efficiency of the battery. Summary of the invention
[0003] In view of this, the present application provides an electrolyte, a sodium ion battery and an electrical device, wherein the electrolyte improves the deposition density of sodium metal on the surface of the negative electrode plate, and enhances the initial charge and discharge efficiency and cycle performance of the sodium ion battery.
[0004] The present application provides an electrolyte, which includes a sodium salt additive, wherein the sodium salt additive includes a first additive and a second additive, wherein the first additive is a sodium sulfonate salt additive, and the second additive is a fluorine-containing sodium salt additive, and in the electrolyte, the mass fraction of the first additive is less than the mass fraction of the second additive.
[0005] Furthermore, a mass ratio α of the first additive to the second additive satisfies the range: 1 / 500≤α≤1 / 20.
[0006] Furthermore, in the electrolyte, the mass fraction A1 of the sodium salt additive satisfies the range: 0.001%≤A1≤2%.
[0007] Furthermore, the first additive is selected from at least one of sodium dodecyl sulfonate, sodium o-benzoylsulfonimide, sodium polydisulfide propane sulfonate, sodium 3-mercaptopropane sulfonate, sodium alcoholthiopropane sulfonate, and sodium 2,3-dimercaptopropane sulfonate; and the second additive is selected from at least one of sodium difluorooxalatoborate, sodium tetrafluoroborate, and sodium difluorophosphate.
[0008] Furthermore, the electrolyte further comprises a film-forming additive, and a mass ratio β of the sodium salt additive to the film-forming additive satisfies the range: 1 / 1500≤β≤1 / 5.
[0009] Furthermore, in the electrolyte, the mass fraction A2 of the film-forming additive satisfies the range: 0.1%≤A2≤10%.
[0010] The present application provides a sodium ion battery, which comprises: an electrode assembly and an electrolyte provided in the present application, wherein the electrode assembly comprises a negative electrode plate, the negative electrode plate comprises a current collector layer and a conductive layer stacked in layers, and the conductive layer comprises a carbon material; the electrolyte is used to infiltrate at least a portion of the electrode assembly.
[0011] Further, the thickness d1 of the conductive layer satisfies the range of 10 μm ≤ d1 ≤ 50 μm; and / or, on the current collector layer, the coating surface density g of the conductive layer satisfies the range of 5 g / m 2 ≤g≤100g / m 2 .
[0012] Furthermore, when the sodium ion battery is in a fully charged state, the sodium ion battery also includes a deposition layer, the deposition layer is arranged on a side of the conductive layer away from the current collector layer, the deposition layer includes metallic sodium, and a deposition thickness d2 of the deposition layer satisfies the range: 10 μm≤d2≤30 μm.
[0013] Furthermore, when the sodium ion battery is in a fully charged state, a shedding rate of metallic sodium σ1≤0.1%; wherein the shedding rate of metallic sodium σ1=m1 / (m1+m2)×100%, m1 is the mass of the shed metallic sodium, and m2 is the mass of the metallic sodium remaining in the deposition layer.
[0014] Furthermore, when the sodium ion battery is in a fully discharged state, the shedding rate σ2 of the conductive layer is ≤0.01%; wherein the shedding rate of the conductive layer σ2=m3 / (m3+m4)×100%, wherein m3 is the weight of the fallen-off portion of the conductive layer, and m4 is the weight of the non-fall-off portion of the conductive layer.
[0015] The present application also provides an electrical device, which includes: a device body and a sodium ion battery provided in the present application, and the sodium ion battery is used to power the device body.
[0016] In the present application, the electrolyte includes a sodium salt additive. When the electrolyte is applied to a sodium ion battery, the sodium salt additive is used to induce the sodium ions in the electrolyte to deposit on the surface of the negative electrode plate and form a sodium metal layer, and improve the deposition density of the sodium metal on the surface of the negative electrode plate, and improve the adhesion performance of the sodium metal layer to the negative electrode plate, thereby reducing the probability of the sodium metal layer falling off due to the expansion of the conductive layer of the negative electrode plate, and facilitating the sodium ions to continue to deposit on the surface of the negative electrode plate during the subsequent charge and discharge process of the sodium ion battery, thereby improving the initial charge and discharge efficiency and cycle performance of the sodium ion battery. When the electrolyte is applied to a sodium ion battery and the sodium ion battery is in a charging state, the first additive has a strong electrophilicity, and the second additive has a strong electron-withdrawing property. The first additive and the second additive jointly induce and capture the sodium ions released from the positive electrode plate. After the first additive reduces the sodium ions to sodium atoms, it induces the sodium atoms to form a dense and uniform sodium metal layer on the surface of the negative electrode plate. Furthermore, as the charging voltage of the sodium ion battery increases, the second additive preferentially undergoes a reduction reaction compared to other components in the electrolyte and forms an SEI film on the surface of the negative electrode sheet, and finally forms a complete SEI film on the periphery of the sodium metal layer, so as to effectively isolate the sodium metal layer and the electrolyte, inhibit the side reaction of sodium and the electrolyte, and help reduce the loss of metallic sodium and maintain the activity of the sodium metal layer. In addition, during the charging process of the sodium ion battery, sodium atoms are deposited on the surface of the negative electrode sheet, and during the discharging process of the sodium ion battery, sodium atoms are released from the surface of the negative electrode sheet and form sodium ions. In other words, the formation of the SEI film and the deposition of the sodium metal layer will occur cyclically during each charge and discharge process of the sodium ion battery. In the electrolyte, the mass fraction of the first additive is less than the mass fraction of the second additive, so that the second additive forms an SEI film containing sodium fluoride on the surface of the negative electrode sheet to isolate the sodium metal layer and the electrolyte, maintain the activity of the sodium metal layer, improve the utilization rate of sodium in the charge and discharge cycle, and ultimately improve the first charge and discharge efficiency and cycle performance of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the implementation will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 A schematic cross-sectional structure diagram of a sodium ion battery according to an embodiment of the present application;
[0019] Figure 2A schematic cross-sectional structure diagram of a negative electrode sheet according to an embodiment of the present application;
[0020] Figure 3 The initial state is a comparison chart of the electrolyte conductivity of Example 2, Comparative Example 1, Comparative Example 3, Comparative Example 5 and Comparative Example 6;
[0021] Figure 4 A comparison diagram of the sodium deposition of the negative electrode sheets of Example 2, Comparative Example 1, Comparative Example 3, Comparative Example 5 and Comparative Example 6 after the sodium ion battery is formed and in a fully charged state;
[0022] Figure 5 It is a comparison diagram of the peeling of the conductive layer of the negative electrode sheets of Example 2, Comparative Example 1, Comparative Example 3, Comparative Example 5 and Comparative Example 6 when the sodium ion battery is cycled and in a fully discharged state;
[0023] Figure 6 This is a scanning electron microscope spectrum of the negative electrode sheet of Example 2 in the initial state;
[0024] Figure 7 This is a scanning electron microscope spectrum of the negative electrode sheet of Example 2 when the sodium ion battery is in a fully discharged state;
[0025] Figure 8 A circuit block diagram of an electrical device according to an embodiment of the present application;
[0026] Fig. 9 This is a schematic diagram of the structure of an electrical device according to an embodiment of the present application.
[0027] Description of reference numerals:
[0028] 100 - sodium ion battery, 110 - electrolyte, 120 - electrode assembly, 121 - negative electrode plate, 1211 - current collector layer, 1212 - conductive layer, 122 - positive electrode plate, 123 - diaphragm, 200 - electrical equipment, 210 - equipment body. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0030] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.
[0031] Reference to "embodiment" or "implementation" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiment or implementation may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0032] With the development of battery technology, in order to meet the demand for higher energy density, the application of traditional negative electrode plates is limited due to the volume expansion of silicon-based materials in the active material layer. Therefore, the negative electrode-free battery system has become a new research direction. In the negative electrode-free system, the negative electrode is mainly coated with a conductive layer current collector. During the battery charging process, the sodium ions released from the positive electrode are deposited on the conductive coating to form a sodium metal negative electrode. However, the conductive coating has poor density and a rough surface. When sodium is deposited on the conductive coating, a small amount of sodium penetrates the conductive coating and is embedded in the conductive coating or penetrates between the conductive coating and the current collector layer. After deposition or peeling, the conductive coating expands, and the adhesion between the conductive coating and the current collector layer is reduced, causing the conductive coating to fall off, affecting the further deposition of sodium, and ultimately making the adhesion performance of sodium on the conductive coating poor, thereby reducing the initial charge and discharge efficiency of the battery.
[0033] See also Figure 1 The present application provides an electrolyte 110, wherein the electrolyte 110 includes a sodium salt additive, wherein the sodium salt additive includes a first additive and a second additive, wherein the first additive is a sodium sulfonate salt additive, and the second additive is a fluorine-containing sodium salt additive, and in the electrolyte 110, the mass fraction of the first additive is less than the mass fraction of the second additive.
[0034] It can be understood that in the electrolyte 110 , the mass fraction of the first additive is the ratio of the mass of the first additive to the mass of the electrolyte 110 ; the mass fraction of the second additive is the ratio of the mass of the second additive to the mass of the electrolyte 110 .
[0035] It can be understood that the electrolyte 110 of the embodiment of the present application is applied to the sodium ion battery 100. The sodium ion battery 100 also includes an electrode assembly 120, the electrode assembly 120 includes a negative electrode sheet 121, and the negative electrode sheet 121 includes a current collector layer 1211 and a conductive layer 1212 stacked. During the charging process of the sodium ion battery 100, the sodium ions in the electrolyte 110 are reduced to sodium atoms on the surface of the negative electrode sheet 121 and form a sodium metal layer. As the charging voltage gradually increases, the second additive forms an SEI film (Solid Electrolyte Interface Membrane) at the interface between the negative electrode sheet 121 and the electrolyte 110; when the sodium ion battery 100 is in a fully charged state, the sodium ions are deposited on the surface of the negative electrode sheet 121, and the second additive continues to form an SEI film to isolate the sodium metal layer and the electrolyte 110.
[0036] It can be understood that the first additive includes a sulfonic acid group, and the first additive is compounded by a small molecule sulfur-containing organic matter and other functional groups, so that the first additive is conducive to the formation of crystal nuclei, refines the grains, and makes the crystal nuclei densely distributed, so as to promote the sodium atoms to be deposited evenly, densely and smoothly on the surface of the negative electrode plate 121.
[0037] It can be understood that the second additive is a fluorine-containing sodium salt, and the fluorine atoms in the second additive form a CF bond with carbon. The bond energy of the CF bond is stronger than the single bond formed between other elements and carbon. Therefore, the second additive is difficult to be reduced, so that the second additive has a lower reduction potential than other components in the electrolyte 110.
[0038] In this embodiment, the electrolyte 110 includes a sodium salt additive. When the electrolyte 110 is applied to the sodium ion battery 100, the sodium salt additive is used to induce the sodium ions in the electrolyte 110 to deposit on the surface of the negative electrode plate 121 and form a sodium metal layer, and improve the deposition density of the sodium metal on the surface of the negative electrode plate 121, and enhance the adhesion performance of the sodium metal layer to the negative electrode plate 121, thereby reducing the probability of the sodium metal layer falling off due to the expansion of the conductive layer 1212 of the negative electrode plate 121, and facilitating the sodium ions to continue to deposit on the surface of the negative electrode plate 121 during the subsequent charge and discharge process of the sodium ion battery 100, thereby improving the initial charge and discharge efficiency and cycle performance of the sodium ion battery 100.
[0039] Specifically, the first additive is a sodium sulfonate salt additive, and the sulfonic acid group in the first additive has strong electrophilicity, so that the first additive has a strong adsorption effect, and the first additive can be adsorbed on the convex protrusions, active sites or special crystal surfaces with large surface tension of the negative electrode plate 121, and the sulfonate anions of the first additive are used to capture sodium ions, and the sodium ions are reduced to sodium atoms by means of the electrophilicity of the sulfonic acid group, so that the sodium atoms located on the surface of the negative electrode plate 121 are induced to migrate on the surface of the negative electrode plate 121, so that the sodium atoms located on the surface of the negative electrode plate 121 are The sodium atoms on the surface migrate to the depressions on the surface of the negative electrode sheet 121 and enter the lattice of the sodium metal layer, so that the deposition layer of the sodium atoms on the surface of the negative electrode sheet 121 is dense and flat, and is tightly combined with the negative electrode sheet 121, so as to improve the adhesion performance of the sodium metal layer and the negative electrode sheet 121. When the sodium ion battery 100 is discharged, compared with the partial deposition of the sodium atoms inside the negative electrode sheet 121 and escaping from the negative electrode sheet 121, the sodium atoms provided in this solution directly fall off from the sodium metal layer, reducing the probability of the conductive layer 1212 of the negative electrode sheet 121 expanding and falling off due to the escaping of the sodium atoms. Further, the second additive contains fluorine atoms, which have a strong electron-withdrawing effect. The electron-withdrawing effect of fluorine helps to distribute negative charges, so as to reduce the lattice energy of the second additive, promote the dissolution of the fluorine-containing sodium salt in the organic solvent, and at the same time can capture the sodium ions escaping from the positive electrode sheet 122, and induce the deposition of sodium on the surface of the negative electrode sheet 121. In addition, the second additive is a fluorine-containing sodium salt additive, and the second additive has a lower reduction potential than other components in the electrolyte 110, so that when the voltage of the sodium ion battery 100 reaches the reduction potential and before the first additive induces sodium ion deposition, the second additive preferentially undergoes a reduction reaction compared to other components in the electrolyte 110, and forms a SEI film (Solid Electrolyte Interface Membrane) containing sodium fluoride on the surface of the negative electrode plate 121. The SEI film containing sodium fluoride is dense and stable, which can effectively reduce the internal resistance of the sodium ion battery 100, and after the sodium atom deposition is completed, the second additive continues to form and repair the SEI film, so that when the sodium ion battery 100 is in a fully charged state, the SEI film is dense and complete, so as to effectively isolate the sodium metal layer and the electrolyte 110, inhibit the side reaction of sodium and the electrolyte 110, and is conducive to reducing the loss of metallic sodium and maintaining the activity of the metallic sodium layer. Furthermore, both the first additive and the second additive contain a large amount of sodium ions, and the sodium ions are present in the electrolyte 110 in a free state, which is convenient for replenishing sodium ions for the electrolyte 110, increasing the amount of sodium ions in the sodium ion battery 100, and improving the initial charge and discharge efficiency of the sodium ion battery 100.
[0040] In this embodiment, when the electrolyte 110 is applied to the sodium ion battery 100 and the sodium ion battery 100 is in a charging state, the first additive has a strong electrophilicity, the second additive has a strong electron-withdrawing property, the first additive and the second additive jointly induce and capture the sodium ions released from the positive electrode plate 122, and the first additive reduces the sodium ions to sodium atoms, and then induces the sodium atoms to form a dense and uniform sodium metal layer on the surface of the negative electrode plate 121. Further, as the charging voltage of the sodium ion battery 100 increases, the second additive preferentially undergoes a reduction reaction compared to other components in the electrolyte 110 and forms an SEI film on the surface of the negative electrode plate 121, and finally forms a complete SEI film on the periphery of the sodium metal layer, so as to effectively isolate the sodium metal layer and the electrolyte 110, inhibit the side reaction of sodium and the electrolyte 110, and help reduce the loss of metallic sodium and maintain the activity of the sodium metal layer. In addition, during the charging process of the sodium ion battery 100, sodium atoms are deposited on the surface of the negative electrode plate 121, and during the discharging process of the sodium ion battery 100, sodium atoms are released from the surface of the negative electrode plate 121 to form sodium ions. In other words, the formation of the SEI film and the deposition of the sodium metal layer will occur cyclically during each charging and discharging process of the sodium ion battery 100. In the electrolyte 110, the mass fraction of the first additive is less than the mass fraction of the second additive, which facilitates the second additive to form a SEI film containing sodium fluoride on the surface of the negative electrode plate 121 to isolate the sodium metal layer and the electrolyte 110, maintain the activity of the sodium metal layer, improve the utilization rate of sodium in the charging and discharging cycle, and ultimately improve the initial charging and discharging efficiency and cycle performance of the sodium ion battery 100.
[0041] Optionally, in some embodiments, the mass fraction of the first additive ranges from 0.002% to 0.02%.
[0042] Specifically, the mass fraction of the first additive may be, but is not limited to, 0.002%, 0.003%, 0.005%, 0.008%, 0.009%, 0.01%, 0.012%, 0.014%, 0.015%, 0.017%, 0.018%, 0.019% and 0.02%, etc.
[0043] In this embodiment, when the mass fraction of the first additive satisfies the range of 0.002% to 0.02%, in the electrolyte 110, the mass fraction of the first additive is within a reasonable range, and in the electrolyte 110, the number of sulfonic acid groups of the first additive is within a reasonable range. On the one hand, the first additive can fully play the role of inducing sodium ions to deposit on the surface of the negative electrode plate 121, so that during the charging process of the sodium ion battery 100, the sodium ions form a dense and uniform sodium metal layer on the surface of the negative electrode plate 121, thereby improving the initial charge and discharge efficiency and cycle performance of the sodium ion battery 100. On the other hand, excessive loss of sodium ions due to an excessive number of sulfonic acid groups can be avoided, further improving the initial charge and discharge efficiency of the sodium ion battery 100. When the mass fraction of the first additive is too large, the number of sulfonic acid groups of the first additive in the electrolyte 110 is too large, so that the first additive may adsorb too many sodium ions and reduce more sodium ions to sodium atoms, thereby causing the loss of sodium ions in the electrolyte 110. When the electrolyte 110 is applied to the sodium ion battery 100, the initial charge and discharge efficiency of the sodium ion battery 100 may be reduced. When the mass fraction of the first additive is too small, the number of sulfonic acid groups of the first additive in the electrolyte 110 is too small, making it difficult to effectively induce the sodium ions in the electrolyte 110 to form a dense and uniform sodium metal layer on the surface of the negative electrode plate 121. If the sodium atoms are deposited unevenly on the surface of the negative electrode sheet 121 and part of the sodium atoms are embedded in the interior of the negative electrode sheet 121, then during the discharge process, the sodium atoms may break the structure of the negative electrode sheet 121 and cause the conductive layer 1212 of the negative electrode sheet 121 to fall off, thereby reducing the performance of the negative electrode sheet 121 and shortening the cycle life of the sodium ion battery 100.
[0044] Optionally, in some embodiments, the mass fraction of the second additive ranges from 0.1% to 1.0%.
[0045] Specifically, the mass fraction of the second additive can be, but is not limited to, 0.1%, 0.12%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.5%, 0.6%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9% and 1.0%, etc.
[0046] In this embodiment, when the mass fraction of the second additive satisfies the range of 0.1% to 1.0%, the mass fraction of the second additive is within a reasonable range. On the one hand, during the charging process of the sodium ion battery 100, the second additive can preferentially reduce other substances in the electrolyte 110 and form a dense and stable SEI film on the surface of the negative electrode plate 121. When the sodium ion battery 100 is in a fully charged state and the sodium metal layer is deposited, a complete SEI film can be formed on the periphery of the sodium metal layer to effectively isolate the sodium metal layer and the electrolyte 110, inhibit the side reaction of sodium and the electrolyte 110, and help reduce the loss of metallic sodium and maintain the activity of the metallic sodium layer, improve the utilization rate of sodium in the charge and discharge cycle process, and ultimately improve the first charge and discharge efficiency and cycle performance of the sodium ion battery 100. On the other hand, it can avoid the thickness of the SEI film formed by the second additive on the surface of the negative electrode plate 121 being too large to increase the impedance of the sodium ion battery 100, so that the sodium ion battery 100 has a higher first charge and discharge efficiency. When the mass fraction of the second additive is too large, the thickness of the SEI film formed by the reaction of the second additive and the surface of the negative electrode sheet 121 during the charging process of the sodium ion battery 100 is too large, which increases the impedance of the sodium ions in the electrolyte 110 in the sodium ion battery 100, thereby reducing the initial charge and discharge efficiency of the sodium ion battery 100. When the mass fraction of the second additive is too small, during the charging process of the sodium ion battery 100, during the deposition process of the sodium metal layer, the electron-withdrawing effect of the second additive is weakened, so that the efficiency of the second additive in inducing and capturing the deposition of sodium ions is reduced, so that the sodium is not deposited tightly on the surface of the negative electrode sheet 121, and the adhesion performance of the sodium metal layer deposited on the surface of the negative electrode sheet 121 and the negative electrode sheet 121 is reduced, and finally the initial charge and discharge efficiency of the sodium ion battery 100 is reduced when the electrolyte 110 is applied to the sodium ion battery 100. Furthermore, when the sodium ion battery 100 is in a fully charged state and the sodium metal layer is deposited, it is difficult for the second additive to form a complete SEI film on the surface of the sodium metal layer, so that the sodium metal layer may partially contact the electrolyte 110 and react with the electrolyte 110, thereby increasing the loss of metallic sodium, reducing the utilization rate of sodium during the charge and discharge cycle, and ultimately reducing the initial charge and discharge efficiency and cycle performance of the sodium ion battery 100.
[0047] In some embodiments, the mass ratio α of the first additive to the second additive satisfies the range: 1 / 500≤α≤1 / 20.
[0048] Specifically, the value of α can be, but is not limited to, 1 / 500, 1 / 480, 1 / 450, 1 / 400, 1 / 350, 1 / 320, 1 / 300, 1 / 250, 1 / 230, 1 / 200, 1 / 180, 1 / 150, 1 / 130, 1 / 100, 1 / 80, 1 / 50, and 1 / 20, etc.
[0049] In this embodiment, when the mass ratio α of the first additive to the second additive satisfies the range of 1 / 500≤α≤1 / 20, in the electrolyte 110, the mass of the first additive and the mass of the second additive are both within a reasonable range, and in the electrolyte 110, the number of sulfonic acid groups of the first additive and the number of fluorine-containing groups of the second additive are both within a reasonable range. On the one hand, the first additive can fully play the role of inducing sodium ions to deposit on the surface of the negative electrode sheet 121, so that during the charging process of the sodium ion battery 100, the sodium ions form a dense and uniform sodium metal layer on the surface of the negative electrode sheet 121, thereby improving the initial charge and discharge efficiency and cycle performance of the sodium ion battery 100. On the other hand, during the charging process of the sodium ion battery 100, the second additive can preferentially reduce other substances in the electrolyte 110 and form a dense and stable SEI film on the surface of the negative electrode plate 121. When the sodium ion battery 100 is in a fully charged state, the SEI film is dense and complete to effectively isolate the sodium metal layer and the electrolyte 110, inhibit the side reaction of sodium and the electrolyte 110, and help reduce the loss of metallic sodium and maintain the activity of the metallic sodium layer. In addition, excessive loss of sodium ions due to excessive number of sulfonic acid groups can be avoided, and the thickness of the SEI film formed by the second additive on the surface of the negative electrode plate 121 can be avoided to increase the impedance of the sodium ion battery 100, so that the sodium ion battery 100 has a higher first charge and discharge efficiency when the electrolyte 110 is applied to the sodium ion battery 100. When the mass ratio α of the first additive to the second additive is too large, in the electrolyte 110, the mass fraction of the first additive is too large or the mass fraction of the second additive is too small. If the mass fraction of the first additive is too large, the first additive may adsorb too many sodium ions and reduce more sodium ions to sodium atoms, thereby causing the loss of sodium ions in the electrolyte 110; if the mass fraction of the second additive is too small, during the charging process of the sodium ion battery 100, it is difficult for the second additive to form an SEI film on the surface of the negative electrode plate 121, and the sodium metal layer may partially contact the electrolyte 110 and react with the electrolyte 110, increasing the loss of metallic sodium, reducing the utilization rate of sodium during the charge and discharge cycle, and ultimately reducing the initial charge and discharge efficiency and cycle performance of the sodium ion battery 100. When the mass ratio α of the first additive to the second additive is too small, in the electrolyte 110, the mass fraction of the first additive is too small or the mass fraction of the second additive is too large. If the mass fraction of the first additive is too small, it is difficult for the first additive to effectively induce the sodium ions in the electrolyte 110 to form a dense and uniform sodium metal layer on the surface of the negative electrode plate 121.If the mass fraction of the second additive is too large, during the charging process of the sodium ion battery 100, the second additive reacts and forms a SEI film with a thickness that is too large on the surface of the negative electrode plate 121, which increases the difficulty for the sodium ions in the electrolyte 110 to enter or escape from the negative electrode plate 121 through the SEI film, increases the impedance of the sodium ions in the sodium ion battery 100, and ultimately reduces the initial charge and discharge efficiency and cycle performance of the sodium ion battery 100.
[0050] Preferably, the mass ratio α of the first additive to the second additive is in the range of 1 / 150≤α≤1 / 50.
[0051] Specifically, the value of α may be, but is not limited to, 1 / 150, 1 / 130, 1 / 100, 1 / 80, 1 / 50, etc.
[0052] In some embodiments, in the electrolyte 110 , the mass fraction A1 of the sodium salt additive satisfies the range: 0.001%≤A1≤2%.
[0053] Specifically, the mass fraction A1 of the sodium salt additive can be, but is not limited to, 0.001%, 0.002%, 0.005%, 0.008%, 0.01%, 0.015%, 0.02%, 0.04%, 0.06%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% and 2%, etc.
[0054] It can be understood that in the electrolyte 110 , the mass fraction of the sodium salt additive is the ratio of the mass of the sodium salt additive to the mass of the electrolyte 110 .
[0055] In this embodiment, when the mass fraction A1 of the sodium salt additive satisfies the range of: 0.001%≤A1≤2%, the mass fraction of the sodium salt additive is within a reasonable range, and the sodium salt additive can fully play the role of inducing and capturing sodium ions in the electrolyte 110 and forming a sodium metal layer on the surface of the negative electrode sheet 121, so as to improve the deposition density of sodium metal on the surface of the negative electrode sheet 121, and improve the adhesion performance of the sodium metal layer and the negative electrode sheet 121, thereby reducing the probability of the sodium metal layer falling off due to the expansion of the conductive layer 1212 of the negative electrode sheet 121, and facilitating the sodium ions to continue to deposit on the surface of the negative electrode sheet 121 during the subsequent charge and discharge process of the sodium ion battery 100, thereby improving the initial charge and discharge efficiency and cycle performance of the sodium ion battery 100. In addition, the situation that the SEI film is too thick or consumes too many sodium ions due to the excessive mass fraction of the sodium salt additive can be prevented, so that the sodium ion battery 100 has a higher initial charge and discharge efficiency and cycle performance. When the mass fraction of the sodium salt additive is too large, the sodium salt additive has a stronger effect of inducing and capturing sodium ions in the electrolyte 110 and forming a sodium metal layer on the surface of the negative electrode plate 121, but correspondingly, the sodium salt additive may reduce excessive sodium ions into sodium atoms, resulting in the loss of sodium ions in the electrolyte 110. Furthermore, when the sodium ion battery 100 is in a fully charged state, the sodium salt additive forms and repairs the SEI film on the surface of the sodium metal layer. The greater the mass fraction of the sodium salt additive, the greater the thickness of the SEI film, which in turn increases the resistance of sodium ions entering or escaping from the negative electrode plate 121 through the SEI film, and increases the internal resistance of the sodium ion battery 100, thereby reducing the initial charge and discharge efficiency of the sodium ion battery 100. When the mass fraction of the sodium salt additive is too small, it is difficult for the sodium salt additive to fully play the role of inducing the sodium ions in the electrolyte 110 to be deposited on the surface of the negative electrode sheet 121, and due to the unevenness of the conductive layer 1212, the deposition of sodium metal on the surface of the negative electrode sheet 121 is not tight enough, or part of the sodium metal enters the interior of the negative electrode sheet 121. When the sodium ion battery 100 is in a discharge state, the sodium metal embedded in the negative electrode sheet 121 may cause the conductive layer 1212 to expand during the process of escaping from the negative electrode sheet 121, and increase the probability of the conductive layer 1212 of the negative electrode sheet 121 and the current collector layer 1211 being peeled off, thereby possibly causing the conductive layer 1212 of the negative electrode sheet 121 to fall off. Furthermore, when the sodium ion battery 100 is in a fully charged state, it is difficult for the sodium salt additive to form a complete SEI film on the surface of the sodium metal layer, so that the sodium metal layer may partially contact the electrolyte 110 and react with the electrolyte 110, thereby increasing the loss of metallic sodium, reducing the utilization rate of sodium during the charge and discharge cycle, and ultimately reducing the initial charge and discharge efficiency and cycle performance of the sodium ion battery 100.
[0056] Preferably, in the electrolyte 110 , the mass fraction A1 of the sodium salt additive satisfies the range: 0.01%≤A1≤1.0%.
[0057] Specifically, the mass fraction A1 of the sodium salt additive may be, but is not limited to, 0.01%, 0.03%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% and 1.0%, etc.
[0058] In some embodiments, the first additive is selected from at least one of sodium dodecyl sulfonate, sodium o-benzoylsulfonimide, sodium polydisulfide propane sulfonate, sodium 3-mercaptopropane sulfonate, sodium thiopropane sulfonate, and sodium 2,3-dimercaptopropane sulfonate; the second additive is selected from at least one of sodium difluorooxalatoborate, sodium tetrafluoroborate, and sodium difluorophosphate.
[0059] It is understood that sodium o-benzoylsulfonimide is sodium saccharin.
[0060] In this embodiment, among the first additives, sodium dodecyl sulfate, sodium o-benzoylsulfonyl imide, sodium polydisulfide propane sulfonate, sodium 3-mercaptopropane sulfonate, sodium thioalcohol propane sulfonate, and sodium 2,3-dimercaptopropane sulfonate all include sulfonic acid groups, which have strong electrophilicity, and the sulfonate anions can induce the capture of sodium ions and reduce the sodium ions to sodium atoms, so as to induce the deposition of sodium atoms on the surface of the negative electrode plate 121, promote the formation of crystal nuclei of sodium atoms, refine the grains, and make the crystal nuclei densely distributed, so as to promote the deposition of sodium atoms on the surface of the negative electrode plate 121 to be uniform, dense and smooth, and ultimately improve the adhesion performance between the sodium metal layer and the negative electrode plate 121. Among the second additives, sodium fluorooxalatoborate, sodium tetrafluoroborate, and sodium difluorophosphate all contain fluorine atoms. On the one hand, the electron-withdrawing effect of fluorine atoms can cooperate with the sulfonic acid groups to induce and capture sodium ions to be densely deposited on the surface of the negative electrode plate 121. On the other hand, the SEI film containing sodium fluoride formed by the second additive has strong stability and density, which can effectively reduce the impedance of the sodium ion battery 100, so that the sodium ion battery 100 has better cycle performance.
[0061] In some embodiments, the electrolyte 110 further includes a film-forming additive, and a mass ratio β of the sodium salt additive to the film-forming additive satisfies the range: 1 / 1500≤β≤1 / 5.
[0062] Specifically, the value of β can be, but is not limited to, 1 / 1500, 1 / 1200, 1 / 1000, 1 / 800, 1 / 500, 1 / 480, 1 / 450, 1 / 400, 1 / 350, 1 / 320, 1 / 300, 1 / 250, 1 / 230, 1 / 200, 1 / 180, 1 / 150, 1 / 130, 1 / 100, 1 / 80, 1 / 50, 1 / 20, 1 / 10 and 1 / 5, etc.
[0063] It can be understood that in the electrolyte 110, the mass fraction of the sodium salt additive is less than the mass fraction of the film-forming additive.
[0064] It can be understood that during the charging process of the sodium ion battery 100, the second additive reaches the reduction potential earlier than the film-forming additive, and the second additive undergoes a reduction reaction preferentially compared to the film-forming additive.
[0065] In this embodiment, the electrolyte 110 also includes a film-forming additive. During the charging process of the sodium ion battery 100, the second additive preferentially reaches a reduction potential and forms a SEI film on the surface of the negative electrode plate 121. As the charging voltage increases, the film-forming additive reaches a reduction potential and also undergoes a reduction reaction on the surface of the negative electrode plate 121, and repairs the SEI film to further improve the density and uniformity of the SEI film, thereby slowing down the loss of sodium ions in the electrolyte 110, thereby improving the cycle performance of the sodium ion battery 100. When the mass ratio β of the sodium salt additive to the film-forming additive satisfies the range of 1 / 1500≤β≤1 / 5, in the electrolyte 110, the mass of the sodium salt additive and the mass of the film-forming additive are both within a reasonable range. On the one hand, the sodium salt additive is used to induce the sodium ions in the electrolyte 110 to deposit on the surface of the negative electrode sheet 121 and form a sodium metal layer, and improve the deposition density of the sodium metal on the surface of the negative electrode sheet 121, and enhance the adhesion performance of the sodium metal layer to the negative electrode sheet 121, thereby reducing the probability of the sodium metal layer falling off due to the expansion of the conductive layer 1212 of the negative electrode sheet 121, so that in the subsequent charge and discharge process of the sodium ion battery 100, the sodium ions continue to be deposited on the surface of the negative electrode sheet 121, thereby improving the initial charge and discharge efficiency and cycle performance of the sodium ion battery 100. On the other hand, the film-forming additive can promote the repair of the SEI film to further improve the compactness and uniformity of the SEI film, slow down the loss of sodium ions in the electrolyte 110, and thus improve the cycle performance of the sodium ion battery 100. When the mass ratio β of the sodium salt additive to the film-forming additive is too large, the mass fraction of the sodium salt additive is too large or the mass fraction of the film-forming additive is too small. If the mass fraction of the sodium salt additive is too large, the sodium salt additive may reduce too many sodium ions to sodium atoms and increase the loss of sodium ions in the electrolyte 110, thereby reducing the utilization rate of sodium ions in the electrolyte 110; if the mass fraction of the film-forming additive is too small, the compactness and uniformity of the SEI film formed on the surface of the negative electrode plate 121 may be poor, increasing the internal resistance of the sodium ion battery 100, thereby reducing the initial charge and discharge efficiency and cycle performance of the sodium ion battery 100.When the mass ratio β of the sodium salt additive to the film-forming additive is too small, the mass fraction of the sodium salt additive is too small or the mass fraction of the film-forming additive is too large. If the mass fraction of the sodium salt additive is too small, it is difficult for the sodium salt additive to fully play the role of inducing the sodium ions in the electrolyte 110 to deposit on the surface of the negative electrode plate 121, and the deposition of sodium metal on the surface of the negative electrode plate 121 is not dense enough, which increases the probability of the conductive layer 1212 expanding and causing the sodium metal layer to fall off, thereby reducing the initial charge and discharge efficiency and cycle performance of the sodium ion battery 100. If the mass fraction of the film-forming additive is too large, the thickness of the SEI film formed on the surface of the negative electrode plate 121 is too large, which increases the impedance of the sodium ions entering or escaping from the negative electrode plate 121 through the SEI film, thereby reducing the initial charge and discharge efficiency of the sodium ion battery 100.
[0066] Preferably, the mass ratio β of the sodium salt additive to the film-forming additive satisfies the range: 1 / 800≤β≤1 / 100.
[0067] In some embodiments, in the electrolyte 110 , the mass fraction A2 of the film-forming additive satisfies the range: 0.1%≤A2≤10%.
[0068] Specifically, the mass fraction A2 of the film-forming additive can be but is not limited to 0.1%, 0.5%, 0.8%, 1%, 1.2%, 2%, 2.5%, 3%, 3.5%, 4%, 5%, 6%, 7%, 8%, 9%, 9.5% and 10%, etc.
[0069] It can be understood that in the electrolyte 110 , the mass fraction of the film-forming additive is the ratio of the mass of the film-forming additive to the mass of the electrolyte 110 .
[0070] In this embodiment, when the mass fraction A2 of the film-forming additive satisfies the range of: 0.1%≤A2≤10%, the mass fraction of the film-forming additive is within a reasonable range, and the film-forming additive cooperates with the second additive to form a complete, dense, uniform and moderately thick SEI film on the surface of the negative electrode plate 121, so that the sodium metal layer and the electrolyte 110 can be isolated, and the sodium metal layer is prevented from contacting the electrolyte 110 and reacting with the electrolyte 110, thereby slowing down the loss of metallic sodium, improving the utilization rate of sodium in the charge and discharge cycle process, and avoiding increasing the impedance of sodium ions entering or escaping from the negative electrode plate through the SEI film, so that when the electrolyte 110 is applied to the sodium ion battery 100, the sodium ion battery 100 has a higher initial charge and discharge efficiency and better cycle performance. When the mass fraction of the film-forming additive is too large, the thickness of the SEI film formed on the surface of the negative electrode plate 121 is too large, which increases the impedance of sodium ions entering or escaping from the negative electrode plate 121 through the SEI film, and reduces the initial charge and discharge efficiency of the sodium ion battery 100. When the mass fraction of the film-forming additive is too small, the density and uniformity of the SEI film formed on the surface of the negative electrode plate 121 may be poor, which increases the internal resistance of the sodium ion battery 100, thereby reducing the initial charge and discharge efficiency and cycle performance of the sodium ion battery 100.
[0071] Preferably, the mass fraction A2 of the film-forming additive satisfies the range: 0.5%≤A2≤5%. Specifically, the mass fraction A2 of the film-forming additive may be, but is not limited to, 0.5%, 0.8%, 1%, 1.2%, 2%, 2.5%, 3%, 3.5%, 4% and 5%.
[0072] Optionally, the film-forming additive is selected from at least one of fluoroethylene carbonate (FEC), ethylene sulfate (DTD), 4-methylethylene sulfate (MDTD), 4-propylethylene sulfate (PDTD), diethyl sulfite (DES), 1,3-propane sultone (PS), ethylene sulfite (ES), propenyl-1,3-sultone (PST), and 1,3-propylene glycol cyclic sulfate (PCS).
[0073] Optionally, the electrolyte 110 further includes a solvent, and the solvent is used to dissolve the sodium salt additive and the film-forming additive, and the solvent is an ether solvent.
[0074] In this embodiment, the solvent is an ether solvent. Compared with ester solvents, the ether solvent provided in this embodiment has lower viscosity, higher dielectric constant and higher solubility. The ether solvent has a higher compatibility with sodium metal to reduce the decomposition of the solvent during the charge and discharge process, so that the interface between the negative electrode plate 121 and the electrolyte 110 has better stability. However, correspondingly, the ether solvent has poor oxidation resistance and is easy to form a passivation film on the surface of the sodium metal layer, consuming a small amount of solvent. In addition, when sodium ions are deposited on the negative electrode plate 121, due to certain defects in the negative electrode plate 121 and its microscopic roughness, more sodium ions are deposited at the local defective positions. On the one hand, the defective parts are easy to become crystal nuclei to induce sodium ions to form sodium clusters, which gradually grow into needle-like whiskers, causing micro-short circuits in the battery, and also accelerating the decomposition of the ether electrolyte 110; on the other hand, the loosely deposited sodium makes its specific surface area larger, and it contacts more electrolyte 110, and the amount of solvent consumed to form a passivation film is also greatly increased, and the quality of the passivation film is difficult to guarantee. When the loose sodium layer forms the SEI film, the amount of reversible sodium ions consumed is also increased, thereby reducing the first efficiency of the battery. Therefore, it is necessary to add the first additive and the second additive to the electrolyte 110 to comprehensively improve the performance of the solvent. Specifically, the electrophilicity of the sulfonic acid group in the first additive can weaken the interaction between the solvent and the sodium ions, reduce the deintercalation energy barrier of the sodium ions at the interface between the negative electrode plate 121 and the electrolyte 110, facilitate the solvation and desolvation of the sodium ions, improve the stability of the interface between the negative electrode plate 121 and the electrolyte 110, and make it easy for the sodium ions to deposit on the surface of the negative electrode plate 121. In addition, during the charging process of the sodium ion battery 100, the second additive preferentially reacts with the solvent to inhibit the decomposition of the ether solvent, slow down the generation of peroxides by the ether solvent, and repair the rough surface of the negative electrode plate 121 to a certain extent, so as to reduce the formation of sodium clusters and reduce the consumption of reversible sodium ions. The first additive, the second additive and the ether solvent of this embodiment cooperate with each other to make the electrolyte 110 have better performance.
[0075] Optionally, in the electrolyte 110, the mass fraction of the solvent satisfies the range of 60% to 95%. Specifically, the mass fraction of the solvent may be, but is not limited to, 60%, 65%, 68%, 70%, 72%, 75%, 80%, 85%, 90%, 95%, etc.
[0076] Optionally, the ether solvent includes a chain ether solvent and a cyclic ether solvent, wherein the number of carbon atoms in the chain ether solvent is greater than or equal to four, and the number of carbon atoms in the cyclic ether solvent is greater than or equal to three.
[0077] In this embodiment, the ether solvent includes a chain ether solvent and a cyclic ether solvent. When the number of atoms of the chain ether solvent is greater than or equal to four, the chain ether solvent has good reduction stability and oxidation stability, and can improve the stability of the solvent to avoid the solvent being decomposed during the charge and discharge process to produce side reactions, so as to improve the stability of the interface between the negative electrode plate 121 and the electrolyte 110. The chain ether solvent reacts synergistically with the second additive and the film-forming additive to form a SEI film of appropriate thickness, density and stability at the interface between the negative electrode plate 121 and the electrolyte 110. When the number of carbon atoms of the cyclic ether solvent is greater than or equal to three, the cyclic ether solvent has a higher ion conductivity, which is convenient for transmitting sodium ions and improving the efficiency of sodium ion deposition on the surface of the negative electrode plate 121, and is conducive to improving the density of the sodium metal layer deposited on the surface of the negative electrode plate 121. Furthermore, the chain ether solvent and the cyclic ether solvent are compounded so that the solvent has better low-temperature performance, thereby improving the low-temperature performance of the electrolyte 110 .
[0078] Optionally, the number of carbon atoms in the chain ether solvent ranges from four to ten. Specifically, the number of carbon atoms in the chain ether solvent is one of four, five, six, seven, eight, nine and ten.
[0079] Optionally, the number of carbon atoms in the cyclic ether solvent ranges from three to five. Specifically, the number of carbon atoms in the cyclic ether solvent is one of three, four and five.
[0080] Optionally, in the electrolyte 110 , the mass fraction A3 of the chain ether solvent satisfies the range: 30%≤A3≤60%; the mass fraction A4 of the cyclic ether solvent satisfies the range: 20%≤A4≤50%.
[0081] Specifically, the mass fraction A3 of the chain ether solvent can be, but is not limited to, 30%, 32%, 35%, 40%, 42%, 45%, 48%, 50%, 52%, 56%, 58% and 60%, etc.
[0082] Specifically, the mass fraction A4 of the cyclic ether solvent may be, but is not limited to, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 40%, 42%, 45% and 50%, etc.
[0083] In the electrolyte 110 provided in this embodiment, the mass fraction of the chain ether solvent and the mass fraction of the cyclic ether solvent are both within a reasonable range, so that the solvent has good reduction stability and oxidation stability, and can avoid the solvent being decomposed to produce side reactions during the charge and discharge process, and the solvent reacts synergistically with the second additive and the film-forming additive to form a SEI film of appropriate thickness, density and stability at the interface between the negative electrode plate 121 and the electrolyte 110, so as to reduce the consumption of reversible sodium ions in the electrolyte 110, facilitate the transmission of sodium ions and improve the efficiency of sodium ion deposition on the surface of the negative electrode plate 121, which is conducive to improving the density of the sodium metal layer deposited on the surface of the negative electrode plate 121. In addition, the solvent has good low temperature performance.
[0084] Optionally, the solvent is selected from at least one of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, tetrahydrofuran, 2-methyltetrahydrofuran and crown ether.
[0085] Optionally, the electrolyte 110 further includes a sodium salt, which provides more sodium ions to the electrolyte 110 , and the solvent is used to dissolve the sodium salt.
[0086] Optionally, the concentration of the sodium salt ranges from 0.01mol / L to 10mol / L. Specifically, the concentration of the sodium salt may be, but is not limited to, 0.01mol / L, 0.05mol / L, 0.1mol / L, 0.5mol / L, 0.8mol / L, 1mol / L, 1.2mol / L, 1.5mol / L, 1.8mol / L, 2mol / L, 2.2mol / L, 2.5mol / L, 3mol / L, 3.2mol / L, 4mol / L, 4.5mol / L, 5mol / L, 6mol / L, 7mol / L, 8mol / L, 9mol / L, and 10mol / L.
[0087] Preferably, the concentration of the sodium salt ranges from 0.1 mol / L to 3 mol / L. Specifically, the concentration of the sodium salt may be, but is not limited to, 0.1 mol / L, 0.5 mol / L, 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, 2 mol / L, 2.2 mol / L, 2.5 mol / L and 3 mol / L.
[0088] Optionally, the sodium salt is selected from at least one of sodium perchlorate, sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, sodium trifluoromethylsulfonate, sodium bis(oxalatoborate) and sodium bis(trifluoromethylsulfonyl)imide.
[0089] Optionally, the conductivity γ of the electrolyte 110 satisfies the range: 2.0 mS / cm≤γ≤12.0 mS / cm.
[0090] Specifically, the value of the conductivity γ of the electrolyte 110 can be but is not limited to 2.0mS / cm, 2.5mS / cm, 3.0mS / cm, 3.5mS / cm, 4.0mS / cm, 4.5mS / cm, 5mS / cm, 6mS / cm, 7mS / cm, 8mS / cm, 9mS / cm, 10mS / cm, 11mS / cm and 12mS / cm, etc.
[0091] In the electrolyte 110 provided in this embodiment, the first additive and the second additive jointly induce and capture the sodium ions released from the positive electrode plate 122. After the first additive reduces the sodium ions to sodium atoms, it induces the sodium atoms to form a dense and uniform sodium metal layer on the surface of the negative electrode plate 121. Further, as the charging voltage of the sodium ion battery 100 increases, the second additive preferentially undergoes a reduction reaction compared to other components in the electrolyte 110 and forms an SEI film on the surface of the negative electrode plate 121, and finally forms a complete SEI film on the periphery of the sodium metal layer, so as to effectively isolate the sodium metal layer and the electrolyte 110, inhibit the side reaction of sodium with the electrolyte 110, and help reduce the loss of metallic sodium and maintain the activity of the sodium metal layer. In addition, the second additive and the film-forming additive are combined to form a complete SEI film on the surface of the negative electrode plate 121 to slow down the side reaction of the electrolyte 110 and ultimately make the electrolyte 110 have better conductivity, thereby improving the initial charge and discharge efficiency of the sodium ion battery 100 when the electrolyte 110 is applied to the sodium ion battery 100.
[0092] Please also see Figure 2 The present application provides a sodium ion battery 100, which includes: an electrode assembly 120 and an electrolyte 110 provided in the present application, wherein the electrode assembly 120 includes a negative electrode plate 121, and the negative electrode plate 121 includes a stacked current collector layer 1211 and a conductive layer 1212, wherein the conductive layer 1212 includes a carbon material; the electrolyte 110 is used to infiltrate at least a portion of the electrode assembly 120.
[0093] Optionally, in some embodiments, the carbon material is activated carbon.
[0094] It can be understood that the charging process of the sodium ion battery 100 is divided into three stages. In the first stage, the sodium ions in the electrolyte 110 are reduced to sodium atoms on the surface of the negative electrode plate 121 and form a sodium metal layer; in the second stage, as the charging voltage gradually increases, the second additive forms a SEI film (Solid Electrolyte Interface Membrane) at the interface between the negative electrode plate 121 and the electrolyte 110, accompanied by the deposition of sodium atoms on the surface of the negative electrode plate 121, that is, the SEI film is in a broken state at this time; in the third stage, the sodium ion battery 100 is in a fully charged state, the sodium metal layer stops depositing, and the second additive and the film-forming additive continue to form a dense, uniform and complete SEI film on the periphery of the sodium metal layer to isolate the sodium metal layer and the electrolyte 110.
[0095] In this embodiment, the negative electrode sheet 121 includes a current collector layer 1211 and a conductive layer 1212 which are stacked, and the conductive layer 1212 is used to improve the conductivity of the negative electrode sheet 121. When the electrolyte 110 infiltrates at least a portion of the electrode assembly 120, the sodium salt additive induces the sodium ions in the electrolyte 110 to deposit on the surface of the conductive layer 1212 and form a dense sodium metal layer, thereby reducing the probability of sodium entering the conductive layer 1212 or between the current collector layer 1211 and the conductive layer 1212, improving the deposition density of sodium metal on the surface of the negative electrode sheet 121, and improving the adhesion of the sodium metal layer to the negative electrode sheet 121, thereby reducing the probability of the sodium metal layer falling off due to the expansion of the conductive layer 1212 of the negative electrode sheet 121, and facilitating the continued deposition of sodium ions on the surface of the negative electrode sheet 121 during the subsequent charge and discharge process of the sodium ion battery 100, so that the sodium ion battery 100 has a higher initial charge and discharge efficiency and better cycle performance.
[0096] Optionally, the current collector layer 1211 is selected from copper foil, aluminum foil, titanium foil, stainless steel foil, graphite carbon paper, aluminum foil coated with conductive agent, copper foil coated with conductive agent, titanium foil coated with conductive agent, stainless steel foil coated with conductive agent, preferably aluminum foil coated with conductive agent, copper foil coated with conductive agent, stainless steel foil coated with conductive agent. The conductive agent is selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0097] Optionally, the electrode assembly 120 also includes a positive electrode plate 122 and a separator 123, the positive electrode plate 122, the separator 123 and the negative electrode plate 121 are stacked in sequence, the positive electrode plate 122 includes a positive electrode material, and the positive electrode material is selected from at least one of sodium vanadium phosphate, sodium vanadium fluorophosphate, sodium iron phosphate, sodium iron pyrophosphate, and composite sodium iron phosphate, and the separator 123 is selected from one of a polypropylene separator 123 and a polyimide film.
[0098] In some embodiments, the thickness d1 of the conductive layer 1212 satisfies the range: 10 μm≤d1≤50 μm.
[0099] Specifically, the thickness d1 of the conductive layer 1212 may be, but is not limited to, 10 μm, 12 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, etc.
[0100] It can be understood that the thickness of the conductive layer 1212 can be measured by a micrometer.
[0101] In this embodiment, when the thickness d1 of the conductive layer 1212 satisfies the range of 10 μm ≤ d1 ≤ 50 μm, the thickness of the conductive layer 1212 is within a reasonable range, so that when the sodium ion battery 100 is charged, sodium atoms can be deposited on the surface of the conductive layer 1212, reducing the probability of sodium atoms entering the conductive layer 1212 or between the conductive layer 1212 and the current collector layer 1211. The conductive layer 1212 cooperates with the sodium salt additive to improve the performance of the sodium metal layer deposited on the surface of the negative electrode sheet 121, and improve the bonding performance between the sodium metal layer and the conductive layer 1212, thereby reducing the probability of the sodium metal layer falling off due to the expansion of the conductive layer 1212 of the negative electrode sheet 121, so that in the subsequent charging and discharging process of the sodium ion battery 100, sodium ions continue to be deposited on the surface of the negative electrode sheet 121, thereby improving the initial charge and discharge efficiency and cycle performance of the sodium ion battery 100. When the thickness of the conductive layer 1212 is too large, the adhesion between the conductive layer 1212 and the current collector layer 1211 is poor, so that the conductive layer 1212 and the sodium metal layer are easily detached from the current collector layer 1211, and during the discharge process of the sodium ion battery 100, the expansion of the conductive layer 1212 is more obvious, which also reduces the deposition performance of the sodium metal layer on the surface of the negative electrode plate 121, thereby reducing the initial charge and discharge efficiency of the sodium ion battery 100. When the thickness of the conductive layer 1212 is too small, the conductive layer 1212 is too thin, and during the charging process of the sodium ion battery 100, the sodium ions in the electrolyte 110 are easily reduced to sodium atoms and enter the conductive layer 1212, or pass through the conductive layer 1212 and enter the gap between the conductive layer 1212 and the current collector layer 1211. During the discharge process of the sodium ion battery 100, the probability of the conductive layer 1212 expanding and falling off due to the deintercalation of sodium atoms is increased, and the adhesion performance between the sodium metal layer and the negative electrode sheet 121 is reduced.
[0102] Preferably, the thickness d1 of the conductive layer 1212 satisfies the range: 10 μm ≤ d1 ≤ 30 μm. Specifically, the thickness d1 of the conductive layer 1212 may be, but is not limited to, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, 28 μm, 30 μm, etc.
[0103] In some embodiments, on the current collector layer 1211, the coating surface density g of the conductive layer 1212 satisfies the range of: 5 g / m 2 ≤g≤100g / m 2 .
[0104] Specifically, the coating surface density g of the conductive layer 1212 may be, but is not limited to, 5 g / m 2 , 10g / m 2 , 15g / m 2 , 20g / m 2 , 25g / m 2 , 30g / m 2 , 35g / m 2 , 40g / m 2 , 45g / m 2 , 50g / m 2 , 55g / m 2 , 60g / m 2 , 65g / m 2 , 70g / m 2 , 75g / m 2 , 80g / m 2 , 85g / m 2 , 90g / m 2 , 95g / m 2 and 100g / m 2 wait.
[0105] It can be understood that the coating surface density of the conductive layer 1212 is the coating mass of the conductive layer 1212 per unit area of the current collector layer 1211 , and the coating surface density of the conductive layer 1212 is calculated by the ratio of the mass of the conductive coating to the area of the current collector layer 1211 .
[0106] It can be understood that the coating surface density of the conductive layer 1212 can characterize the "foil leakage rate" of the negative electrode plate 121. The larger the coating surface density of the conductive layer 1212, the lower the foil leakage rate of the negative electrode plate 121, and the smaller the coating surface density of the conductive layer 1212, the higher the foil exposure rate of the negative electrode plate 121.
[0107] In this embodiment, when the coating surface density g of the conductive layer 1212 satisfies the range of 5 g / m 2 ≤g≤100g / m 2When , the coating surface density g of the conductive layer 1212 is within a reasonable range. During the charging process of the sodium ion battery 100, sodium atoms can be deposited on the surface of the conductive layer 1212, reducing the probability of sodium atoms entering the conductive layer 1212 or between the conductive layer 1212 and the current collector layer 1211. The conductive layer 1212 cooperates with the sodium salt additive to improve the performance of the sodium metal layer deposited on the surface of the negative electrode sheet 121, and improve the bonding performance between the sodium metal layer and the conductive layer 1212, thereby reducing the probability of the sodium metal layer falling off due to the expansion of the conductive layer 1212 of the negative electrode sheet 121, so that in the subsequent charging and discharging process of the sodium ion battery 100, sodium ions continue to be deposited on the surface of the negative electrode sheet 121, thereby improving the initial charge and discharge efficiency and cycle performance of the sodium ion battery 100. When the coating surface density of the conductive layer 1212 is too large, if part of the sodium metal enters the gap between the conductive layer 1212 and the current collector layer 1211, during the discharge process of the sodium ion battery 100, it is more difficult for the sodium metal to escape from the conductive layer 1212, so that the conductive layer 1212 is easy to peel off from the current collector layer 1211, and the performance of the negative electrode plate 121 is reduced. When the coating surface density of the conductive layer 1212 is too small, it is difficult for the conductive layer 1212 to cover the current collector layer 1211, and the exposure rate of the negative electrode plate 121 is too high, so that when the sodium ion battery 100 is in a charging state, most of the sodium metal may be directly deposited on the surface of the current collector layer 1211, which increases the probability of the conductive layer 1212 and the current collector layer 1211 peeling off, which is not conducive to the dense deposition of sodium metal on the surface of the negative electrode plate 121.
[0108] Preferably, the coating surface density g of the conductive layer 1212 satisfies the range: 2 g / m 2 ≤g≤50g / m 2 Specifically, the coating surface density g of the conductive layer 1212 may be, but is not limited to, 2 g / m 2 , 5g / m 2 , 10g / m 2 , 15g / m 2 , 20g / m 2 , 30g / m 2 , 40g / m 2 and 50g / m 2 wait.
[0109] In some embodiments, when the sodium ion battery 100 is in a fully charged state, the sodium ion battery 100 further includes a deposition layer, wherein the deposition layer is disposed on a side of the conductive layer 1212 away from the current collector layer 1211 , the deposition layer includes sodium, and a deposition thickness d2 of the deposition layer satisfies the range: 10 μm ≤ d2 ≤ 30 μm.
[0110] Specifically, the deposition thickness d2 of the deposition layer may be, but is not limited to, 10 μm, 11 μm, 12 μm, 15 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, 25 μm, 26 μm, 28 μm, 29 μm, 30 μm, etc.
[0111] It can be understood that the deposited layer is a sodium metal layer.
[0112] Optionally, the test conditions for the deposition thickness of the deposited layer are: forming the sodium ion battery 100 under the conditions of 25°C, 0.1C, 2.5V to 3.5V, and 100% SOC, wherein charging the sodium ion battery 100 under the conditions of 25°C, 0.1C, 2.5V to 3.5V, and 100% SOC means that the temperature of the sodium ion battery 100 during charging is 25°C, and it is charged with a current of one tenth of the battery capacity, and the voltage range of the formation process is 2.5V to 3.5V. SOC is the abbreviation of "State of Charge", which represents the remaining power or charging state of the sodium ion battery 100, and is used to describe the amount of charge that the battery has been charged relative to the total capacity of the battery. 100% SOC means that the sodium ion battery 100 is in a fully charged state.
[0113] In this embodiment, when the deposition thickness d2 of the deposition layer satisfies the range: 10μm≤d2≤30μm, the deposition thickness of the deposition layer is within a reasonable range, the deposition layer can maintain good adhesion to the negative electrode plate 121, and the deposition layer has good compactness. During the discharge process of the sodium ion battery 100, the sodium in the deposition layer can be converted into sodium ions and fall off, so that the sodium ion battery 100 has a higher initial charge and discharge efficiency, better cycle performance and higher energy density. When the deposition thickness of the deposition layer is too large, the mass of the deposition layer is too large, and it is easy to fall off from the conductive layer 1212 as a whole, thereby reducing the initial charge and discharge efficiency of the sodium ion battery 100. When the deposition thickness of the deposition layer is too small, too little sodium metal is deposited in the deposition layer, which makes the energy density of the sodium ion battery 100 too low.
[0114] In some embodiments, when the sodium ion battery 100 is in a fully charged state, the shedding rate of metallic sodium σ1≤0.1%; wherein the shedding rate of metallic sodium σ1=m1 / (m1+m2)×100%, m1 is the mass of the metallic sodium shed, and m2 is the mass of the metallic sodium remaining in the deposition layer.
[0115] Specifically, the value of the shedding rate σ1 of metallic sodium can be but is not limited to 0.001%, 0.002%, 0.005%, 0.008%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09% and 0.1%, etc.
[0116] Optionally, the test conditions for the shedding rate of metallic sodium are as follows: after the sodium ion battery 100 is formed under the conditions of 25°C, 0.1C, 2.5V to 3.5V, and 100% SOC, the sodium ion battery 100 is disassembled, and the mass m1 of the metallic sodium shed is the mass of the metallic sodium shed from the deposited layer during the disassembly process, and m1+m2 is the mass of the metallic sodium in the deposited layer before disassembly.
[0117] In this embodiment, when the sodium ion battery 100 is in a fully charged state, the shedding rate σ1 of the metallic sodium in the deposited layer is ≤0.1%, and the shedding rate of the metallic sodium in the deposited layer is extremely low, so the sodium has good deposition performance and adhesion performance on the surface of the negative electrode plate 121. The negative electrode plate 121, the sodium salt additive and the film-forming additive cooperate with each other to improve the deposition density of the sodium metal on the surface of the negative electrode plate 121, and enhance the adhesion performance of the sodium metal layer to the negative electrode plate 121, thereby reducing the probability of the sodium metal layer falling off due to the expansion of the conductive layer 1212 of the negative electrode plate 121, so that in the subsequent charge and discharge process of the sodium ion battery 100, the sodium ions continue to be deposited on the surface of the negative electrode plate 121, so that the sodium ion battery 100 has a higher initial charge and discharge efficiency and better cycle performance.
[0118] In some embodiments, when the sodium ion battery 100 is in a fully discharged state, the shedding rate σ2 of the conductive layer 1212 is ≤0.01%; wherein the shedding rate σ2 of the conductive layer 1212 is m3 / (m3+m4)×100%, wherein m3 is the weight of the fallen portion of the conductive layer 1212, and m4 is the weight of the unfallen portion of the conductive layer 1212.
[0119] It can be understood that when the sodium ion battery 100 is in a fully discharged state, the power in the sodium ion battery 100 is close to zero and is in a 0% SOC state, and during the discharge process, the sodium metal layer is converted into sodium ions and falls off from the negative electrode, and the sodium metal layer is no longer deposited on the surface of the negative electrode plate 121.
[0120] Specifically, the value of the shedding rate σ2 of the conductive layer 1212 can be, but is not limited to, 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, 0.01%, etc.
[0121] Optionally, the test conditions for the shedding rate of the conductive layer 1212 are as follows: after the sodium ion battery 100 is cyclically charged and discharged five times under the conditions of 25° C., 0.1C, and 2.5V to 3.5V, the sodium ion battery 100 is in a fully discharged state, and the sodium ion battery 100 is disassembled. The weight m3 of the fallen-off part of the conductive layer 1212 is the mass of the part of the conductive layer 1212 that falls off during the disassembly process, and m3+m4 is the mass of the negative electrode sheet 121 minus the mass of the current collector layer 1211.
[0122] In this embodiment, when the sodium ion battery 100 is in a fully charged state, the shedding rate σ2 of the conductive layer 1212 is ≤0.01%, and the shedding rate of the conductive layer 1212 is extremely low, then the conductive layer 1212 and the current collector layer 1211 have excellent bonding performance, this is because sodium has good deposition performance and adhesion performance on the surface of the negative electrode sheet 121, the negative electrode sheet 121, the sodium salt additive and the film-forming additive cooperate with each other to improve the deposition density of sodium metal on the surface of the negative electrode sheet 121, and enhance the adhesion performance of the sodium metal layer and the negative electrode sheet 121, thereby reducing the probability of the sodium metal layer falling off due to the expansion of the conductive layer 1212 of the negative electrode sheet 121, so that in the subsequent charge and discharge process of the sodium ion battery 100, sodium ions continue to be deposited on the surface of the negative electrode sheet 121, so that the sodium ion battery 100 has a higher initial charge and discharge efficiency and better cycle performance.
[0123] The technical solution of this application is further described below in multiple embodiments:
[0124] Example 1 to Example 14, Comparative Example 1 to Comparative Example 8:
[0125] Preparation of sodium ion battery 100:
[0126] 1. Preparation of positive electrode sheet 122:
[0127] The positive electrode active material sodium iron pyrophosphate, conductive carbon black (SP), and adhesive polyvinylidene fluoride (PVDF) are dispersed in a solvent N-methylpyrrolidone (NMP) and mixed evenly to obtain a positive electrode slurry; the positive electrode slurry is coated on a positive electrode collector aluminum foil; after drying, cold pressing, slitting, and cutting, a positive electrode sheet 122 is obtained.
[0128] 2. Preparation of negative electrode sheet 121:
[0129] Activated carbon and adhesive polyvinylidene fluoride (PVDF) are dispersed in solvent N-methylpyrrolidone (NMP) and mixed to form a conductive slurry, which is then coated on the negative electrode current collector aluminum foil. After drying, cold pressing, slitting, and cutting, a stacked current collector layer 1211 and a conductive layer 1212 are obtained, which are used as the negative electrode sheet 121.
[0130] 3. Preparation of electrolyte 110:
[0131] The ether solvent is fully mixed in an argon atmosphere glove box with a moisture content of ≤0.01ppm, and then the sodium salt (sodium hexafluorophosphate) is dissolved in the mixed solvent, stirred until completely and evenly dissolved, and finally the sodium salt additive and the film-forming additive are added, and mixed evenly to obtain the electrolyte 110 of Examples 1 to 14 and Comparative Examples 1 to 8. Among them, in the electrolyte 110 of Examples 1 to 14 and Comparative Examples 1 to 8, the type and mixing mass ratio of the solvent, the type and mass fraction of the first additive, and the type and mass fraction of the second additive are shown in Table 1.
[0132] 4. Preparation of diaphragm 123:
[0133] A polyethylene film is used as the separator 123 .
[0134] 5. Assembly of the sodium ion battery 100:
[0135] By adopting the lamination process, the prepared positive electrode plate 122, the separator 123, and the negative electrode plate 121 are made into a laminated bare cell in order, and the bare cell is assembled in an aluminum-plastic film after welding the pole ears; after vacuum baking, the prepared electrolyte 110 is injected, and the cell is packaged to finally obtain a negative electrode-free sodium ion battery 100, that is, implementing battery 1 to implementing battery 14 and comparative battery 1 to comparative battery 8 are obtained, wherein implementing battery 1 adopts the electrolyte 110 of embodiment 1, implementing battery 2 adopts the electrolyte 110 of embodiment 2, comparative battery 1 adopts the electrolyte 110 of comparative example 1, and comparative battery 2 adopts the electrolyte 110 of comparative example 2, and so on.
[0136] Table 1: Component parameters of the sodium ion batteries 100 of Examples 1 to 14 and Comparative Examples 1 to 8.
[0137]
[0138]
[0139] In Table 2, in the column of solvent types and mixing mass ratios, diethylene glycol dimethyl ether:tetrahydrofuran = 2:1 means that the solvent types include diethylene glycol dimethyl ether and tetrahydrofuran, and the ratio of the mass of diethylene glycol dimethyl ether to the mass of the tetrahydrofuran is 2:1; diethylene glycol dimethyl ether: ethylene glycol diethyl ether: tetrahydrofuran = 2:2:1 means that the solvent types include diethylene glycol dimethyl ether, ethylene glycol diethyl ether and tetrahydrofuran, and the mass of diethylene glycol dimethyl ether: the mass of ethylene glycol diethyl ether: the mass of tetrahydrofuran = 2:2:1, and so on.
[0140] Performance test of sodium ion battery 100:
[0141] The implementation batteries 1 to 14 and the comparative batteries 1 to 8 were placed, formed, shaped, and tested for capacity. The electrolyte 110 injection coefficient was 6.58 g / Ah, and the rated capacity of the battery was 0.280 Ah. The battery voltage window was 2.5 to 3.5 V, and the battery formation was 0.1 C charging to 3.5 V; the battery capacity was 0.1 C discharge to 2.5 V, and the cycle was 3 cycles, and finally 0.1 C discharge to 1.0 V.
[0142] 1. Calculation of the first charge and discharge efficiency of the sodium ion battery 100:
[0143] The first charge and discharge efficiency of the sodium ion battery 100 = first discharge capacity / first charge capacity×100%. The values of the first charge and discharge efficiency of the implementation battery 1 to the implementation battery 14 and the comparison battery 1 to the comparison battery 8 are shown in Table 2.
[0144] 2. Calculation of the shedding rate σ1 of metallic sodium:
[0145] The sodium ion battery 100 in a fully charged state after formation is disassembled in an argon atmosphere glove box (H2O<0.01ppm, O2<0.01ppm), and the shedding rate of the metallic sodium of the negative electrode plate 121 is observed and calculated. The metallic sodium shedding rate is calculated by mass, as follows: ① Electronic balance weighing: weigh the mass M of the negative electrode plate 121 in the initial state 负极 , where M 负极 is the sum of the mass of the current collector layer 1211 and the mass of the conductive layer 1212; when disassembled in the charged state, the sodium metal layer is deposited on the surface of the negative electrode plate 121, and the sum of the mass of the sodium metal layer and the negative electrode plate 121 is M 负极+钠金属层 , the mass of metallic sodium that falls off during disassembly is M 钠 , then M 钠 =m1,M 负极+钠金属层 -M 负极 +M 钠 =m1+m2; ② Under full charge, the shedding rate of metallic sodium = M 钠 / (M 负极+钠金属层 -M 负极 +M 钠 )×100%.
[0146] Among them, the values of the shedding rates σ1 of metallic sodium of implementation batteries 1 to implementation batteries 14 and comparison batteries 1 to comparison batteries 8 in the fully charged state are shown in Table 2.
[0147] 3. Calculation of the shedding rate σ2 of the conductive layer 1212:
[0148] The sodium ion battery 100 in a fully discharged state after capacity separation was disassembled in an argon atmosphere glove box (H2O<0.01ppm, O2<0.01ppm), and the shedding rate of the conductive layer 1212 of the negative electrode sheet 121 was observed and calculated. The shedding rate of the conductive layer 1212 of the negative electrode sheet 121 is calculated by mass, as follows: ① Electronic balance weighing: The mass of the current collector layer 1211 in the initial state is weighed as M 集流体层1211 , the mass of the negative electrode plate 121 is M' 负极 , M' 负极 is the sum of the mass of the current collector layer 1211 and the mass of the conductive layer 1212; when the sodium ion battery 100 is disassembled in a fully discharged state, the weight of the portion of the conductive layer 1212 that falls off is M", then M"=m3, M' 负极 -M 集流体层1211 =m3+m4; ② In the fully charged state, the shedding rate of the conductive layer 1212 is σ2=M” / (M' 负极 -M 集流体层1211 )×100%.
[0149] Among them, the values of the shedding rate σ2 of the conductive layer 1212 of the implementation batteries 1 to the implementation batteries 14 and the comparison batteries 1 to the comparison batteries 8 in the fully discharged state are shown in Table 2.
[0150] Table 2: Performance parameters of implementation batteries 1 to 14 and comparative batteries 1 to 8.
[0151]
[0152]
[0153] Please refer to Table 1 and Table 2. In Comparative Examples 1 to 8, the electrolyte 110 in Comparative Examples 1 and 8 does not have a sodium salt additive and a film-forming additive, the electrolyte 110 in Comparative Examples 2 to 4 includes the first additive, the electrolyte 110 in Comparative Example 5 includes the second additive, the electrolyte 110 in Comparative Example 6 includes a film-forming additive, and the electrolyte 110 in Comparative Example 7 includes the second additive and a film-forming additive. It can be seen from the performance parameters of Comparative Battery 1 and Comparative Battery 8 that when the electrolyte 110 does not contain a sodium salt additive and a film-forming additive, the electrolyte 110 in Comparative Example 4 includes the first additive, the electrolyte 110 in Comparative Example 5 includes the second additive, and the electrolyte 110 in Comparative Example 6 includes a film-forming additive. When any additive is added, the initial efficiency of the sodium ion battery 100 is low, the adhesion between the sodium metal layer and the negative electrode plate 121 is poor, and the negative electrode conductive layer 1212 is severely peeled off. In addition, the components of the solvents of the comparative battery 1 and the comparative battery 8 are different, so that the initial charge and discharge efficiencies of the comparative battery 1 and the comparative battery 8 are roughly the same, but the introduction of ethylene glycol dimethyl ether into the solvent can appropriately improve the deposition performance of the sodium metal layer on the surface of the negative electrode plate 121, and reduce the peeling of the conductive layer 1212 of the negative electrode plate 121 and the current collector layer 1211. It can be concluded from the performance parameters of comparative batteries 2 to 4 that when the first additive is introduced and the mass fraction of the first additive is within a reasonable range, the initial charge and discharge efficiency of the sodium ion battery 100 and the deposition performance of the sodium metal layer on the surface of the negative electrode sheet 121 can be improved within an appropriate range, and the peeling of the conductive layer 1212 of the negative electrode sheet 121 and the current collector layer 1211 can be reduced. The degree of improvement is related to the amount of the first additive added, but the degree of improvement is still limited. From the data of comparative battery 5, it can be seen that the introduction of the second additive can improve the initial charge and discharge efficiency of the sodium ion battery 100, but the improvement effect is not obvious. Accordingly, the second additive can improve the deposition performance of the sodium metal layer on the surface of the negative electrode sheet 121, and reduce the peeling of the conductive layer 1212 of the negative electrode sheet 121 and the current collector layer 1211. It can be seen from the data of comparative battery 6 and comparative battery 7 that, without adding the sodium salt additive, simply adding the film-forming additive cannot effectively improve the initial charge and discharge efficiency of the sodium ion battery 100, and it is difficult to improve the deposition performance of the sodium metal layer on the surface of the negative electrode sheet 121, and it is difficult to improve the bonding performance of the conductive layer 1212 and the current collector layer 1211. Accordingly, when the second additive is compounded with the film-forming additive, the second additive and the film-forming additive can improve the initial charge and discharge efficiency of the sodium ion battery 100, but the improvement effect is not obvious. The second additive can also improve the deposition performance of the sodium metal layer on the surface of the negative electrode sheet 121, and reduce the peeling of the conductive layer 1212 of the negative electrode sheet 121 and the current collector layer 1211, which corresponds to the performance parameters of comparative battery 5.
[0154] Please refer to Examples 1 to 3, and Examples 5 to 10. It can be seen from the data of Battery 1 to Battery 3 that, under the same other conditions, when the mass fraction of the first additive satisfies a reasonable range, the corresponding sodium ion battery 100 has a higher initial charge and discharge efficiency, and the shedding rate σ1 of metallic sodium and the shedding rate σ2 of the conductive layer 1212 are both 0. In other words, the first additive can well improve the deposition of the sodium metal layer on the surface of the negative electrode sheet 121, and can effectively prevent the conductive layer 1212 from falling off the current collector layer 1211. Similarly, it can be seen from the data of implementation batteries 5 to implementation batteries 7 that, under the same other conditions, when the mass fraction of the first additive satisfies a reasonable range, the corresponding sodium ion battery 100 has a higher first charge and discharge efficiency, but in the electrolyte 110 of Examples 5 to 7, the type of the second additive is sodium difluorooxalatoborate, and in the electrolyte 110 of Examples 1 to 3, the type of the second additive is sodium tetrafluoroborate, which means that under the same other conditions, the effect of sodium difluorooxalatoborate in improving the deposition density of the sodium metal layer is worse than the effect of sodium tetrafluoroborate in improving the deposition density of the sodium metal layer, so that the first charge and discharge efficiency of implementation batteries 5 to 7 is lower than the first charge and discharge efficiency of implementation batteries 1 to 3. Similarly, it can be seen from the data of the implementation battery 8 to the implementation battery 10 that when the mass fraction of the first additive meets the reasonable range, the corresponding sodium ion battery 100 has a higher first charge and discharge efficiency, and the shedding rate σ1 of the metal sodium and the shedding rate σ2 of the conductive layer 1212 are both 0. In other words, the first additive can well improve the deposition of the sodium metal layer on the surface of the negative electrode plate 121, and can effectively prevent the conductive layer 1212 from falling off the current collector layer 1211. In addition, the type of the first additive of the implementation battery 8 to the implementation battery 10 is sodium saccharin, and the type of the first additive of the implementation battery 1 to the implementation battery 3 is sodium dodecyl sulfate. It can be seen from the data in Table 2 that, under the same other conditions, the effect of sodium saccharin in improving the deposition density of the sodium metal layer is the same as the effect of sodium dodecyl sulfate in improving the deposition density of the sodium metal layer, so that the implementation battery 1 to the implementation battery 3, the implementation battery 8 to the implementation battery 10 all have a higher first charge and discharge efficiency.
[0155] Please refer to Example 2, Example 4 and Comparative Example 3. It can be seen from the data of Example 2, Example 4 and Comparative Example 3 that when other conditions are the same and the mass fraction of the first additive is within a reasonable range, as long as the mass fraction of the second additive is within a reasonable range, the corresponding sodium ion battery 100 can maintain a high initial charge and discharge efficiency, and the shedding rate σ1 of metallic sodium and the shedding rate σ2 of the conductive layer 1212 are both low or 0. Correspondingly, if the electrolyte 110 only includes the first additive but not the second additive, the initial charge and discharge efficiency of the corresponding sodium ion battery 100 is reduced, and the shedding rate σ1 of metallic sodium and the shedding rate σ2 of the conductive layer 1212 are high. This shows that when the electrolyte 110 includes the first additive and the second additive at the same time, the first additive and the second additive have a synergistic effect, and the first additive and the second additive jointly induce and capture the sodium ions released from the positive electrode sheet 122. After the first additive reduces the sodium ions to sodium atoms, it induces the sodium atoms to form a dense and uniform sodium metal layer on the surface of the negative electrode sheet 121. Furthermore, as the charging voltage of the sodium ion battery 100 increases, the second additive undergoes a reduction reaction preferentially compared to other components in the electrolyte 110 and forms an SEI film on the surface of the negative electrode plate 121, and finally forms a complete SEI film on the periphery of the sodium metal layer, so as to effectively isolate the sodium metal layer and the electrolyte 110, inhibit the side reaction of sodium and the electrolyte 110, and help reduce the loss of metallic sodium and maintain the activity of the sodium metal layer, improve the utilization rate of sodium in the charge and discharge cycle process, and ultimately improve the initial charge and discharge efficiency and cycle performance of the sodium ion battery 100.
[0156] Similarly, please refer to Example 9 and Example 11. It can be seen from the data of Example 9 and Example 11 that when other conditions are the same and the mass fraction of the first additive is within a reasonable range, as long as the mass fraction of the second additive is within a reasonable range, the corresponding sodium ion battery 100 can maintain a relatively high initial charge and discharge efficiency, and the shedding rate σ1 of metallic sodium and the shedding rate σ2 of the conductive layer 1212 are both low or 0. This shows that: when the electrolyte 110 includes the first additive and the second additive at the same time, the first additive and the second additive have a synergistic effect. The first additive and the second additive jointly induce and capture the sodium ions released from the positive electrode plate 122. After the first additive reduces the sodium ions to sodium atoms, it induces the sodium atoms to form a dense and uniform sodium metal layer on the surface of the negative electrode plate 121. The second additive forms an SEI film on the surface of the negative electrode plate 121, and finally forms a complete SEI film on the periphery of the sodium metal layer to effectively isolate the sodium metal layer and the electrolyte 110, inhibit the side reaction of sodium and the electrolyte 110, which is beneficial to reduce the loss of metallic sodium and maintain the activity of the sodium metal layer, improve the utilization rate of sodium in the charge and discharge cycle process, and finally improve the initial charge and discharge efficiency and cycle performance of the sodium ion battery 100.
[0157] Please refer to Examples 12 to 14. It can be seen from the data of Examples 12 and 13 that when the electrolyte 110 includes the first additive and the second additive and the ratio of the first additive to the second additive is adapted, the introduction of the film-forming additive has no effect on the initial charge and discharge efficiency of the sodium ion battery 100, the deposition of metallic sodium, and the stripping of the conductive layer 1212, further proving that the film-forming additive is mainly used for forming a stable SEI film on the negative electrode sheet 121. It can be seen from the data of Examples 12 and 14 that when the type and mass fraction of the first additive, the type and mass fraction of the second additive, and the type and mass fraction of the film-forming additive are the same, the type of solvent and the mixing mass ratio are changed, and the sodium ion battery 100 still has a high initial charge and discharge efficiency.
[0158] Further, please refer to Example 2, Comparative Example 1, Comparative Example 3, Comparative Example 5 and Comparative Example 6. Figure 3 ,Depend on Figure 3It can be seen that there is no additive in the electrolyte 110 of comparative example 1, the conductivity of the electrolyte 110 is about 6.02mS / cm, and the first efficiency of the sodium ion battery 100 is about 40.58%; the electrolyte 110 of comparative example 3 includes the first additive, the conductivity of the electrolyte 110 is 6.21mS / cm, and the corresponding first efficiency is 54.27%; the electrolyte 110 of comparative example 5 includes the second additive, the conductivity of the electrolyte 110 is 6.28mS / cm, and the corresponding first efficiency of the sodium ion battery 100 is 51.36%. The addition of the first additive and the second additive is beneficial to improve the conductivity of the electrolyte 110, thereby improving the first charge and discharge efficiency of the corresponding sodium ion battery 100. The electrolyte 110 of comparative example 6 includes a film-forming additive, and the conductivity of the electrolyte 110 is 6.05 mS / cm, and the corresponding sodium ion battery 100 is 40.49%, which means that when the first additive and the second additive are not added to the electrolyte 110, the film-forming additive has no effect on improving the conductivity of the electrolyte 110 and the first charge and discharge efficiency of sodium ions. In contrast, the electrolyte 110 of Example 2 includes the first additive and the second additive, and the mass fraction of the first additive and the mass fraction of the second additive are both within a reasonable range, so that the conductivity of the electrolyte 110 of Example 2 is 6.62 mS / cm, and the corresponding first efficiency is 85.98%, which once again verifies that the first additive and the second additive can improve the conductivity of the electrolyte 110, thereby improving the first charge and discharge efficiency of the corresponding sodium ion battery 100.
[0159] Further, please refer to Example 2, Comparative Example 1, Comparative Example 3, Comparative Example 5 and Comparative Example 6. Figure 4 and Figure 5 ,Depend on Figure 4 It can be concluded that when the first additive and the second additive are used in combination, when the sodium ion battery 100 is in a fully charged state, the metal sodium deposition of the negative electrode plate 121 is uniform and dense, and there is no shedding phenomenon. Please refer to the legend of Example 2 for details; when the first additive, the second additive and the film-forming additive are introduced alone, when the sodium ion battery 100 is in a fully charged state, the metal sodium layer of the negative electrode plate 121 shows different degrees of shedding, and the phenomenon of sticking to the diaphragm 123 is serious, but there is no peeling phenomenon of the conductive layer 1212 of the negative electrode plate 121. Please refer to the legends of Comparative Example 1, Comparative Example 3, Comparative Example 5 and Comparative Example 6 for details. Figure 5It can be concluded that when the first additive and the second additive are used in combination, when the sodium ion battery 100 is in a fully discharged state, no sodium metal layer remains on the negative electrode plate 121, and the conductive layer 1212 of the negative electrode plate 121 remains intact without falling off. For details, please refer to the legend of Example 2. When one of the first additive, the second additive and the film-forming additive is introduced alone, when the sodium ion battery 100 is in a fully discharged state, the negative electrode plate 121 shows different degrees of residual metal sodium layer, and the conductive layer 1212 of the negative electrode plate 121 partially falls off. For details, please refer to the legends of Comparative Examples 1, 3, 5 and 6. Figure 4 and Figure 5 It can be seen that when the electrolyte 110 includes the first additive and the second additive, the first additive and the second additive have a synergistic effect, which can effectively improve the deposition of the metal sodium layer on the surface of the negative electrode plate 121 and improve the bonding performance between the conductive layer 1212 and the current collector layer 1211.
[0160] Further, please refer to Example 2, Comparative Example 1, Comparative Example 3, Comparative Example 5 and Comparative Example 6. Figure 6 and Figure 7 ,Depend on Figure 6 and Figure 7 By comparison, it can be concluded that in the initial state, the conductive layer 1212 coated on the current collector is distributed in particles on the surface of the negative electrode sheet 121 of Example 2, and the black area at the connection between the particles is aluminum foil, i.e., the current collector layer 1211. The conductive layer 1212 on the surface of the entire negative electrode sheet 121 is not evenly and densely distributed; when the sodium ion battery 100 is in a fully discharged state, the negative electrode sheet 121 presents the same shape as in the initial state, indicating that adding the first additive and the second additive to the electrolyte 110 of Example 2 can improve the problem of the conductive layer 1212 of the negative electrode sheet 121 falling off. When no additive is introduced, or one of the first additive, the second additive and the film-forming additive is introduced alone, the conductive layer 1212 of the negative electrode plate 121 has poor adhesion due to volume expansion, exhibits different degrees of peeling, and exposes the current collector layer 1211, so that the shedding rate of the conductive layer 1212 and the shedding rate of metallic sodium in Comparative Examples 1, 3, 5 and 6 are higher than the shedding rate of the conductive layer 1212 and the shedding rate of metallic sodium in Example 2. In addition, it can be seen from the data of Comparative Examples 2 to 4 that the introduction of different proportions of the first additive alone has some improvement on the peeling of the conductive layer 1212, but it is still relatively serious overall.
[0161] See also Figure 8 and Fig. 9The present application also provides an electrical device 200 , which includes: a device body 210 and a sodium ion battery 100 provided in the present application, and the sodium ion battery 100 is used to power the device body 210 .
[0162] It can be understood that the sodium ion battery 100 is electrically connected to the device body 210 .
[0163] In this embodiment, the sodium ion battery 100 has a high initial charge and discharge efficiency and cycle performance, so that the sodium ion battery 100 can provide stable power for the device body 210, which is beneficial to improving the user experience.
[0164] Optionally, the power-consuming device 200 of the embodiment of the present application may be, but is not limited to, a portable electronic device such as a mobile phone, a tablet computer, a laptop computer, a desktop computer, a smart bracelet, a smart watch, an e-reader, a game console, etc. It may also be a vehicle such as a car, a truck, a car, a truck, a truck, a motor vehicle, a high-speed train, an electric vehicle, etc. In addition, it may also be various household appliances, etc. The present application Fig. 9 The electrical equipment 200 of the embodiment is an energy storage battery cabinet.
[0165] It can be understood that the electrical equipment 200 described in this embodiment is merely a form of the electrical equipment 200 used by the sodium ion battery 100, and should not be understood as a limitation on the electrical equipment 200 provided in the present application, nor should it be understood as a limitation on the electrical equipment 200 provided in each embodiment of the present application.
[0166] Mentioning "embodiment" and "implementation method" in this application means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrases in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments. In addition, it should also be understood that the features, structures or characteristics described in the various embodiments of the present application can be arbitrarily combined to form another embodiment that does not deviate from the spirit and scope of the technical solution of the present application, provided that there is no contradiction between them.
[0167] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the above preferred implementation modes, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.
Claims
1. An electrolyte, characterized in that: The electrolyte includes a sodium salt additive, which includes a first additive and a second additive, wherein the first additive is a sodium sulfonate additive, and the second additive is a fluorine-containing sodium salt additive. In the electrolyte, the mass fraction of the first additive is less than the mass fraction of the second additive.
2. The electrolyte according to claim 1, characterized in that The mass ratio α of the first additive to the second additive satisfies the range: 1 / 500≤α≤1 / 20.
3. The electrolyte according to claim 1, characterized in that In the electrolyte, the mass fraction A1 of the sodium salt additive satisfies the range: 0.001%≤A1≤2%.
4. The electrolyte according to claim 1, characterized in that The first additive is selected from at least one of sodium dodecyl sulfonate, sodium o-benzoylsulfonimide, sodium polydisulfide propane sulfonate, sodium 3-mercaptopropane sulfonate, sodium thiopropane sulfonate, and sodium 2,3-dimercaptopropane sulfonate; the second additive is selected from at least one of sodium difluorooxalatoborate, sodium tetrafluoroborate, and sodium difluorophosphate.
5. The electrolyte according to any one of claims 1 to 4, characterized in that: The electrolyte further includes a film-forming additive, and a mass ratio β of the sodium salt additive to the film-forming additive satisfies the range: 1 / 1500≤β≤1 / 5.
6. The electrolyte according to claim 5, characterized in that In the electrolyte, the mass fraction A2 of the film-forming additive satisfies the range: 0.1%≤A2≤10%.
7. A sodium ion battery, characterized in that: The sodium ion battery comprises: An electrode assembly, the electrode assembly comprising a negative electrode sheet, the negative electrode sheet comprising a stacked current collector layer and a conductive layer, the conductive layer comprising a carbon material; and The electrolyte according to any one of claims 1 to 6, wherein the electrolyte is used to wet at least a portion of the electrode assembly.
8. The sodium ion battery according to claim 7, characterized in that: The thickness d1 of the conductive layer satisfies the range: 10 μm ≤ d1 ≤ 50 μm; and / or, On the current collector layer, the coating surface density g of the conductive layer meets the range: 5g / m 2 ≤g≤100g / m 2 .
9. The sodium ion battery according to claim 8, characterized in that: When the sodium ion battery is in a fully charged state, the sodium ion battery further includes a deposition layer, the deposition layer is disposed on a side of the conductive layer away from the current collector layer, the deposition layer includes metallic sodium, and a deposition thickness d2 of the deposition layer satisfies the range: 10 μm≤d2≤30 μm.
10. The sodium ion battery according to claim 9, characterized in that: When the sodium ion battery is in a fully charged state, the shedding rate of metallic sodium σ1≤0.1%; wherein the shedding rate of metallic sodium σ1=m1 / (m1+m2)×100%, m1 is the mass of the metallic sodium that has fallen off, and m2 is the mass of the metallic sodium that remains in the deposition layer.
11. The sodium ion battery according to claim 7, characterized in that: When the sodium ion battery is in a fully discharged state, the shedding rate σ2 of the conductive layer is ≤0.01%; wherein the shedding rate σ2 of the conductive layer is m3 / (m3+m4)×100%, wherein m3 is the weight of the shedding portion of the conductive layer, and m4 is the weight of the non-shedding portion of the conductive layer.
12. An electrical device, characterized in that: The electrical equipment includes: Equipment body; The sodium ion battery according to any one of claims 7 to 11, wherein the sodium ion battery is used to power the device body.
Citation Information
Patent Citations
Sodium ion battery
CN114447333A
Sodium ion battery
CN115986194A
Electrolyte and sodium ion battery
CN117219866A
High-initial-efficiency quick-charging sodium-ion battery and application
WO2024120067A1
Electrolyte for sodium-ion battery, and sodium-ion battery
WO2024183399A1
Cited By
Electrolyte, sodium ion battery and electrical device
WO2026092174A1
